Factors Influencing Information Technology Science and Needs Analysis Design for Islamic Religious Education Subjects - Retno Dwi Ramadhannita; Mulyawan Safwandy Nugraha; Ujang Dedih (DIROSAT: Journal of Education, Social Sciences & Humanities, 2025)
In recent years, the development of information technology has been very fast. Information Science and Technology (IST) has become one of the most important fields in the development of modern society. It plays a key role in changing the way we work, communicate, and access information. student needs analysis is carried out to evaluate the program planning that has been implemented and to improve further program planning related to the learning process (design, development, utilization, management, and evaluation). By understanding these needs, the PAI curriculum can be structured more appropriately to meet the expectations of the community and provide an understanding of religion that is relevant to the reality of life. This research article was written using qualitative methods, literature studies, and literature research. The study of literature related to the theory discussed, especially those related to science and technology and the design of the analysis of student needs for Islamic Education subjects. Science and Technology has a significant impact on Islamic Religious Education subjects. The relationship between the two is realized through the use of technology as a means of teaching and learning. Science and technology can be an effective tool to present information and concepts of Islamic religion interactively. The design of student needs analysis has a close relationship with Mat